A Novel Thiophene‐Fused Ending Group Enabling an Excellent Small Molecule Acceptor for High‐Performance Fullerene‐Free Polymer Solar Cells with 11.8% Efficiency. Issue 6 (8th May 2017) - Xie, Dongjun; Liu, Tao; Gao, Wei; Zhong, Cheng; Huo, Lijun; Luo, Zhenghui; Wu, Kailong; Xiong, Wentao; Liu, Feng; Sun, Yanming; Yang, Chuluo
Abstract : In this article, we designed and synthesized a novel small molecule acceptor of ITCPTC with thiophene‐fused ending group by employing a new active methylene precursor of CPTCN. The ITCPTC‐based polymer solar cells with PBT1‐EH as a donor achieved very high power conversion efficiencies (PCEs) of up to 11.8% with a remarkably enhanced fill factor (FF) of 0.751, a near 20% boost in PCE with respect to the ITIC‐based control device. These values are among the highest PCEs and FFs for polymer solar cells (PSCs). In the whole study, we made contrasts with ITIC to understand the reasons of excellent performance of ITCPTC‐based PSCs through various measurements, such as GIXD and RSoXS. We revealed that the simple modification of ITIC into ITCPTC not only change the material electronic structure, but also mediates the material interactions and crystallization, which contribute together to the excellent performance of ITCPTC‐based PSCs. Abstract : A novel small molecule acceptor of ITCPTC with thiophene‐fused ending group is designed and synthesized. The ITCPTC‐based polymer solar cells with PBT1‐EH as donor achieved very high PCEs of up to 11.8% with a remarkably enhanced fill factor of 0.751, a near 20% boost in PCE with respect to the ITIC‐based control device.